2019
DOI: 10.1002/jcph.1380
|View full text |Cite
|
Sign up to set email alerts
|

Is Bioequivalence Established Based on the Reference‐Scaled Average Bioequivalence Approach Relevant to Chronic Administration of Phenytoin? Perspectives Based on Population Pharmacokinetic Modeling and Simulations

Abstract: Phenytoin demonstrates time-dependent and nonlinear pharmacokinetics (PK) within the therapeutic range of 10 to 20 μg/mL. There are discussions on the relevance of bioequivalence (BE) demonstrated in a single-dose BE study in healthy subjects to exposure under chronic use conditions in patients, particularly given that phenytoin has a narrow therapeutic index. The objective of this study was to quantitatively evaluate the appropriateness of singledose PK BE through simulations for the phenytoin extended-capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The virtual simulations of NONMEM ® to study bioequivalence using single and multiple-dose administration to predict C max and steady-state concentrations (SSC), respectively showed that while single-dose administration resulted in significant differences, they might not be sensitive to predict failure in BE for steady-state concentrations [58]. These results were also supported by Kim et al [35]. Kim et al needed to use absorption lag time and fix the maximal nonlinear clearance in NONMEM ® for the PK model to better fit the observed values.…”
Section: Nonmem ®mentioning
confidence: 83%
See 1 more Smart Citation
“…The virtual simulations of NONMEM ® to study bioequivalence using single and multiple-dose administration to predict C max and steady-state concentrations (SSC), respectively showed that while single-dose administration resulted in significant differences, they might not be sensitive to predict failure in BE for steady-state concentrations [58]. These results were also supported by Kim et al [35]. Kim et al needed to use absorption lag time and fix the maximal nonlinear clearance in NONMEM ® for the PK model to better fit the observed values.…”
Section: Nonmem ®mentioning
confidence: 83%
“…For example, to simulate plasma concentrations, input data was used from the different knowledgebase, including predictions from ADMET Predictor™, a module in the GastroPlus™, such as the P eff [24]. In this respect, fitting of the data was common [28,35,45,46] and could be unrealistic [46]. Model equations and physiological parameters were not given and only stated as "default" [46,47].…”
Section: Gastroplus™mentioning
confidence: 99%
“…Bioavailability and bioequivalence studies should be carried out in drugs with a narrow therapeutic range, such as phenytoin, which has a minimum effective concentration of 10 mg/L and an effective maximum of 20 mg/L (43)(44)(45). In this sense, a poor solution or a small change in the dose would lead to changes in bioavailability and plasma levels (46). At the same time, because these types of drugs form strong bonds with plasma proteins (i.e., albumin), they are displaced from binding with usual proteins by drugs that have a higher affinity for those proteins, which generates toxicity when the maximum concentration is exceeded (45).…”
Section: T-1 T-2 T-1 T-2 T-1 T-2mentioning
confidence: 99%
“…These factors should be considered during the planning phase of clinical trials to optimize cost-effectiveness and efficiency in drug development. To address these considerations, approaches integrating PK principles and simulations into drug development have been widely discussed as useful tools for decision-making [12][13][14][15][16][17]. Kim et al [15] studied BE results under scenario 1 (multiple-dose, 2-period, crossover design, BE studies with ABE) and scenario 2 (single-dose,4-period, fully replicated design, BE studies with RSABE) based on a PK-model based simulation.…”
Section: Introductionmentioning
confidence: 99%
“…To address these considerations, approaches integrating PK principles and simulations into drug development have been widely discussed as useful tools for decision-making [12][13][14][15][16][17]. Kim et al [15] studied BE results under scenario 1 (multiple-dose, 2-period, crossover design, BE studies with ABE) and scenario 2 (single-dose,4-period, fully replicated design, BE studies with RSABE) based on a PK-model based simulation. Karalis and Macheras [16] performed a simulation study with PK parameters to compare the method proposed by EMA with existing methods in two-stage BE designs.…”
Section: Introductionmentioning
confidence: 99%